Assessing the Economic Impacts of Food Hubs on Regional Economies: A Framework that Includes Opportunity Cost. (29th April 2016) - Jablonski, B. B. R.; Schmit, T. M.; Kay, D.
Abstract : The number of food hubs—businesses that aggregate and distribute local food—in the United States is growing, fueled in part by increasing public support. However, there have been few data-driven assessments of the economic impacts of these ventures. Using an input-output-based methodology and a unique data set from a successful food hub, we measure net and gross impacts of a policy supporting their development. We estimate a gross output multiplier of 1.75 and an employment multiplier of 2.14. Using customer surveys, we estimate that every $1 increase in final demand for food hub products generates a $0.11 reduction in purchases in other sectors.